2016
DOI: 10.1177/230949901602400126
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty with Extra- or Intra-Articular Correction Technique for Arthritic Knees with Extra-Articular Deformity of the Femur or Tibia: A Report of Three Cases

Abstract: This study reports 3 patients who underwent total knee arthroplasty combined with extra-or intraarticular correction technique for arthritic knees with extra-articular deformity of the femur or tibia.Key words : arthroplasty, replacement, knee; fractures, ununited introduction It is difficult to obtain optimal mechanical alignment through total knee arthroplasty (TKA) in patients with knee deformity, because the deformity (canal sclerosis, crooked canal, or retained hardware) may prevent the use of an intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Similar strategies have also been reported for tibial nonunion. 55 Good outcomes were also reported by Radke and Radke in 10 knees with EADs ≥ 15° where mean preoperative KSS and functional scores improved from 28 and 46.5 to 80.6 and 76 respectively. Devoid of any nonunions, their study cited advantages of EAC such as preservation of collaterals, precise restoration of axes and avoidance of managing bone defects.…”
Section: Simultaneous Single-stage Eac and Tkasupporting
confidence: 53%
See 1 more Smart Citation
“…Similar strategies have also been reported for tibial nonunion. 55 Good outcomes were also reported by Radke and Radke in 10 knees with EADs ≥ 15° where mean preoperative KSS and functional scores improved from 28 and 46.5 to 80.6 and 76 respectively. Devoid of any nonunions, their study cited advantages of EAC such as preservation of collaterals, precise restoration of axes and avoidance of managing bone defects.…”
Section: Simultaneous Single-stage Eac and Tkasupporting
confidence: 53%
“…Nonunion of osteotomy sites is a potential concern for EAC. 55 As a preventive measure, the osteotomy should be carried out through the metaphysis (which has the best healing potential), perfectly reduced with no interposing cement, fixed with rigid, rotationally stable osteosynthesis and reinforced with a rod through the osteotomy site. 13 , 14 Hazratwala et al .…”
Section: Problems With Osteotomiesmentioning
confidence: 99%
“… 19) Generally, the deformed bony anatomy, crooked medullary canal, and retained hardware that preclude an insertion of a conventional system can be overcome by some surgical strategies. 27 28) For instance, Paredes-Carnero et al 29) reported a significant improvement of KSKS, KSFS, and ROM after intra-articular correction for extra-articular deformity (EAD) in 9 TKAs by altering the IM entry point. Loures et al 30) reported significant improvement of Knee Society Score in 25 knees with PTOA, and the mean MA was corrected from 9.3° of valgus to 0.6° of varus alignment with 20% outlier noted, when an EM reference guide of a conventional system was chosen.…”
Section: Discussionmentioning
confidence: 99%